Elimination of undifferentiated cancer cells by pluripotent stem cell inhibitors - Ben-David, Uri; Biran, Alva; Scaffidi, Paola; Herold-Mende, Christel; Boehringer, Markus; Meshorer, Eran; Benvenisty, Nissim (Journal of molecular cell biology, 2014)
Dear Editor,
Gesehen am 18.08.2020